Vesicoureteric reflux and timing of micturating cystourethrography after urinary tract infection. Issue 3 (1st March 1997) - Craig, Jonathan C; Knight, John F; Sureshkumar, Premala; Lam, Albert; Onikul, Ella; Roy, L Paul
Abstract : OBJECTIVE: To test the medical belief that the micturating cystourethrogram (MCU) be deferred four to six weeks after acute symptomatic urinary tract infection (UTI) because of the risk of falsely detecting vesicoureteric reflux if performed earlier. STUDY DESIGN: A cross sectional analytic study of preschool children with first time symptomatic UTI. RESULTS: Of the 284 eligible children, 272 (95.8%) had MCU at a median time of 29 days after diagnosis (range 5 to 167 days). Vesicoureteric reflux was present in 77 children (28.3%). Beyond one week after diagnosis (270 children) the proportion and severity of vesicoureteric reflux detected was not associated with the timing of the MCU. Before one week, both children tested had vesicoureteric reflux. CONCLUSIONS: The presence and grade of vesicoureteric reflux is not influenced by the timing of the MCU one week after acute symptomatic UTI. There may be an association between the MCU and the presence of vesicoureteric reflux for children tested within one week after UTI. The MCU need not be deferred for four to six weeks after UTI.